The fourth estate speaks out: newspapers endorsements’ rebuke of Donald Trump in the 2016 presidential election: O quarto estado se manifesta: a rejeição dos apoios editoriais a Trump na eleição presidencial de 2016 - Almeida Lima, Leandro (Conjuntura internacional, 2018)
The article analyzes the newspapers endorsements in the US in the 2016 presidential election and, in particular, the massive rejection of the Republican nominee Donald Trump. It is argued that it was due to Trump’s non-belonging to mainstream politics and the press tendency to centrism.